The potential of polyurethane foam insulation in roof maintenance / Nur Amirah Damia Md Nasser - Md Nasser, Nur Amirah Damia (2018)
Malaysia has a tropical climate which receives a lot of rainfall throughout the year. Heavy rainfall increases the dampness to roof and causes leakage. Even though numerous solutions are available in the market, this has not stem the tide of these occurrences. Hence, this paper presents the potential of polyurethane foam insulation in roof maintenance. Polyurethane foam insulation insulates and eliminates thermal bridging through fasteners or gaps in decking while providing a long-lasting roofing system. A study has been conducted to identify the issue and problem according to the use of conventional roof insulation. The objective of this study is to evaluate the function of polyurethane foam insulation that can contribute to roof protection. Some of theprevious studies are from the relevant research articles and journals. Based on the data, there are many challenges regarding the arising of building defect and leakages. Service and maintenance after the equipment break down also increases the usage of maintenance cost. Expected outcome will benefit for preventive maintenance.